Digital media and reporting conflict : blogging and the bbc's coverage of war and terrorism - Bennett, Daniel ([S.l.] : Routledge, 2013)
This book explores the impact of new forms of online reporting on the BBC$1 (Bs coverage of war and terrorism. Informed by the views of over 100 BBC staff at all levels of the corporation, Bennett captures journalists$1 (Bshifting attitudes towards blogs and internet sources used to cover wars and other conflicts. He argues that the BBC$1 (Bs practices and values are fundamentally evolving in response to the challenges of immediate digital publication. Ongoing challenges for journalism in the online media environment are identified: maintaining impartiality in the face of calls for more open personal journalism; ensuring accuracy when the power of the "former audience" allows news to break at speed; and overcoming the limits of the scale of the BBC$1 (Bs news operation in order to meet the demands to present news as conversation. While the focus of the book is on the BBC$1 (Bs coverage of war and terrorism, the conclusions are more widely relevant to the evolving practice of journalism at traditional media organizations as they grapple with a revolution in publication.s
Keywords: British Broadcasting Corporation; Great Britain; Journalism--Objectivity; Online journalism; Terrorism--Press coverage; War--Press coverage